2016
DOI: 10.21608/bvmj.2016.31373
|View full text |Cite
|
Sign up to set email alerts
|

Some teratological effects of difloxacin in rats

Abstract: The aim of this experiment was to detect the teratogenic effects of difloxacin in Wister Albino rats. Thirty pregnant rats were divided into 3 groups; group (1) behaved as control and received normal saline. Group (2) was administered difloxacin at a dose of 20 mg/kg b. wt and group (3) was administered difloxacin at a dose of 40 mg/kg b. wt orally once daily from 6 th to 15 th day of pregnancy. The study revealed no teratogenic effect at a dose of 20 mg/kg b. wt, while at a dose of 40 mg/kg b.wt has significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Stahlmann [22] indicated that the administration of ofloxacin and ciprofloxacin to immature animal's induced cardiac hyperplasia. Similarly, Elkomy et al [2], AL-Myahi et al [3], Aboubakr et al [5], and El Komy et al [18] stated that the administration of both norfloxacin and difloxacin induced visceral malformation in pregnant rats.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Stahlmann [22] indicated that the administration of ofloxacin and ciprofloxacin to immature animal's induced cardiac hyperplasia. Similarly, Elkomy et al [2], AL-Myahi et al [3], Aboubakr et al [5], and El Komy et al [18] stated that the administration of both norfloxacin and difloxacin induced visceral malformation in pregnant rats.…”
Section: Discussionmentioning
confidence: 97%
“…Particular drugs can pass the placental barrier and enter the fetal circulation, induce therefore structural abnormalities in the neonate at birth extending to undefined period [2].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained data are supported [40] who reported that, the use of mefenamic acid revealed variable histopathological alterations as mild hepato-cellular necrosis with increased liver weight. Moreover, [38]. noticed that liver sections of piroxicam treated mice showed inflammatory cellular infiltration, vacuolated hepatocytes, dilated sinusoids, and increased number of Kupffer cells.…”
Section: Discussionmentioning
confidence: 98%
“…who reported mild interstitial nephritis associated with fluoroquinolones, norfloxacin, ciprofloxacin and nofloxacin. Also, [36][37][38]. reported that, norfloxacin showed glomerular olization in the lining epithelium of the renal tufts while the intertubular tissue showed focal hemorrhages in kidney after its oral administration.…”
Section: Discussionmentioning
confidence: 99%